Evaluasi Program Penanggulangan Kemiskinan di Kabupaten Sragen - Ardian Y P; D Ghulam Manar; Ahmad Taufiq (Journal of Politic and Government Studies, 2014)
Poverty reduction policies which conducted by UPT-PK become a good innovation to help poor people in Sragen to meet their basic needs. Programs provided in either the health, education, and socio and conomic sector are capable of providing benefits and advantages for poor people, thus it become a manifestation of government concern towards poor people.Practice the existing poverty reduction process is always done based on Standard Operating Procedure (SOP). With the existing procedure, the poverty services will be systematically served in one place (one stop service). Verification mechanism generates database completely valid and trustworthy, so that the goal of the poverty reduction will be reached. The existence of a partnership with the agency or company is able to simultaneously support an optimize all types of existing programs. Commitment to poverty reduction programs given is designed so that the poor have easy access in terms of basic needs. In addition to existed program, UPT-PK should further develop promoting community-based programs so that communities also take an active role in improving their lives. Keywords : UPT-PK, Poverty Reduction, Policy, Programs